Understanding confidentiality breach in adolescent mental health sessions: an integrated model of culture and parenting. Issue 4 (19th May 2021) - Yao, Elvin; Li, Yuhua; Wang, Chunhui; Hui, Jianwen
ABSTRACT: Adolescent mental health has become a growing concern. One unique challenge to adolescents' willingness to seek professional mental health support is the concern of confidentiality breach by their parents. This concern may carry more weight in collectivistic cultures, such as China. The current study utilized a large parent sample (N = 460) recruited from six high schools and attempted to integrate cultural self-construal and parenting styles in the context of parental attitudes toward mental health professionals and desires to breach confidentiality. Parental independent self-construal was related to more positive attitudes toward mental health professionals through higher authoritative parenting and negatively associated with authoritarian parenting. On the other hand, interdependent self-construal was related to less positive attitudes toward mental health professionals via higher authoritarian parenting and lower authoritative parenting. More positive attitudes toward mental health professionals, in turn, were related to lower desire to breach confidentiality. Permissive parenting did not play a significant role in this process. The present study illustrates the importance of understanding culturally specific factors and parental influences in therapeutic practices.